Impact of the COVID-19 Lockdown in Malaysia: An Examination of the Psychological Well-Being of Parent-Child Dyads and Child Behavior in Families With Children on the Autism Spectrum - Fong, Hui Xian; Cornish, Kim; Kirk, Hannah; Ilias, Kartini; Shaikh, Mohd Farooq; Golden, Karen Jennifer (Frontiers in Psychiatry, 2021)
Background The COVID-19 pandemic lockdowns have adversely impacted children on the autism spectrum and their families, especially in Malaysia where this population is sidelined. The current quantitative research aimed to investigate the impact of the Malaysian COVID-19 lockdown on the behaviour and psychological distress of children formally diagnosed with an autism spectrum condition (ASC) as well as the psychological distress and wellbeing of their parents, in comparison with a typically developing (TD) control group. Methods The children’s age ranged between 5 to 17 years. The sample included 72 ASC parent-child dyads and 62 TD parent-child dyads. The primary caregiver completed an online survey including the following: demographic and diagnostic information; ASC symptoms; children’s inattention, hyperactivity/impulsivity, perceived stress, depression and anxiety; parents’ perceived stress, depression, anxiety, and wellbeing based on their experience pre- and mid-lockdown (March 18th to June 9th 2020) in Malaysia. Results Among the ASC group, no significant pre- and mid-lockdown change was found in ASC symptoms (p>.05). There were no significant gender differences (boys/girls) in all the child scales. The 2 (diagnosis [ASC, TD]) × 2 (lockdown [pre-lockdown, mid-lockdown]) mixed-model ANOVAs revealed main effects of lockdown on children’s attention, hyperactivity/impulsivity, anxiety, and parents’ perceived stress, depression and psychological wellbeing (p<.005). There was a main effect of diagnosis in all child and parent variables, except parents’ perceived stress (p>.005). However, there was no significant interaction effect between diagnosis and lockdown (p>.005). All child behavior (inattention and hyperactivity/impulsivity) and child psychological distress (anxiety, depression, and perceived stress) were significantly correlated in both the ASC and TD groups (p<.005). On the other hand, only some of the parent variables were significantly correlated with child variables (p<.0045) in the ASC group while none of the parent variables was significantly correlated with the child variables (p>.005). Conclusion The results provide preliminary evidence indicating negative effects of the Malaysian lockdown on both children on the autism spectrum and TD children, as well as their parents. These quantitative results will be triangulated with the qualitative interview data to provide a holistic understanding of the impact of the pandemic, informing translational policy and practice recommendations.